Sales promotion as a leverage strategy for improving sales and profitability in alcohol beverage industry - Aghara, Vincent N. O.; Nwaizugbo, Ireneus C.; Oparah, Promise C.; Ifeanyichukwu, Chioma D. (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
This paper considered the huge amount of money being expended on sales promotion in recent times and sought to know whether organizations that use such strategy have justification for such investment. It sought to know whether the increase in sales promotion expenses resulted to increase in the organizationsâ sales volume as well as profitability. Nigerian Breweries Plc was used for the study because of its high-level involvement in sales promotion. Personal interview was used to collect relevant information from the key staff of the organization while the published annual report was to collect relevant information from the key staff of the organization while the published annual report was used to source information on the organizationâs performance in terms of sales of sales turnover, marketing expenditure, and profitability. Findings showed that sales promotion was used because the strategy was very effective in developing and sustaining patronage and loyalty among channel members. It was further found that there was a strong positive correlation between sales promotion expenses and sales volume and between sales promotion expenses and profit. It was therefore recommended that organizations should use sales promotion as a strategy for leveraging sales and profit, provided that such organizations manage the sales promotion programmed effectively to generate desired results.